Diagnostic difficulties in case of pleural and chylous effusion in mesothelioma patient - Karpińska-Jazdon, Lidia; Spychalski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2005)
Malignant mesothelioma results in extensive infiltration to mucous membranes. If neoplastic proliferation affects lymphatic vessels or surrounding tissues it may result in the obstruction of lymphatic tracts, an increase in its internal pressure, and eventually, appearance of lymphatic exudate. This paper describes a case of the patient, whose chest and abdominal cavities were gradually filled with chyle. Multidirectional and repeated diagnostics did not lead to the diagnosis within ten months. The patient was initially treated conservatively because of the presence of lymph in the right pleural cavity without success. Therefore, thoracic duct was ligated, and a temporary improvement was achieved. Unfortunately, later on chyle appeared in all parts of the lymphatic tract and thoracic duct, including the chest and abdominal cavity. The diagnosis was finally made after the appearance of metastasis of mesothelioma in lymph nodes. We believe that if a thoracoscopic pleural biopsy or lymphangiography had been performed in the patient in the initial phase of the diagnostic process, the disease would have been diagnosed earlier. Because of the increase in morbidity of pleural mesothelioma, similar cases of untypical course of the disease, whose main symptom is chylous effusion are also likely to be more frequent.